High nature value farmlands: challenges in identification and interpretation using Cyprus as a case study - Zomeni, Maria; Martinou, Angeliki F.; Stavrinides, Menelaos; Vogiatzakis, Ioannis N. (My University, 2018)
High Nature Value Farmland systems (HNVf) in Europe are recognised for their importance for biodiversity conservation and their extent is one of the impact indicators in the CAP monitoring and evaluation framework for the 2014–2020 cycle. Due to differences in farming typologies and data availability between nations, a common methodology for identifying HNVf does not exist, nor is considered appropriate. In the current study we use the Mediterranean island of Cyprus as a case study to highlight EU-wide issues for the identification and mapping of HNVf. We brought together under a common spatial framework datasets on farming typology, agro-chemical inputs, water use intensity and biodiversity data collected from public authorities and nature/biodiversity conservation organisations. Using an expert driven approach informed by a range of stakeholders, we identified and mapped potential HNVf areas employing a 1 km2 mapping grid as the reporting spatial framework under two storylines for defining farmland area within every grid cell: a liberal with 10% threshold and a conservative with 25% threshold. Areas containing potentially HNVf may extend from 22.5–34.5% of the island, depending on the storyline employed. HNVf Type I is the more restricted type for both storylines, while Type II is the most extensive. The highest overlap was between Type II and Type III for the liberal storyline and between Type I and II for the conservative storyline. HNVfs cover an area between 30 to 57% of the Natura2000 network on the island depending on the storyline. With the liberal storyline for farmland definition, the spatial extent of HNVfs together with the existing Natura2000 sites cover 90% of the study area, while with the conservative storyline this figure drops to ca.75%. The results confirm the role of HNVfs within and around Natura2000 sites in Cyprus and their potential for providing connection and site buffering opportunities, particularly in the lowlands, while they can provide information about policy-making for agri-environmental payments targeting.
Keywords: Biodiversity; Conservation; Mediterranean island; Natura2000; Policy-making